PENGARUH CORPORATE ACTION TERHADAP PENGAMBILAN KEPUTUSAN DALAM PEMBELIAN SAHAM (STUDI PADA INVESTOR DI KOTA MAKASSAR) - Ismail Badollahi; A Ifayani Haanurat; Kadriati Hasyim (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2020)
This research uses quantitative methods. This study aims to examine and see the effect of Corporate Action consisting of dividends, right issues and stock split on decision making in purchasing shares. This study uses multiple regression analysis using a sample of 80 respondents, namely investors in the city of Makassar. The analytical tool used is the SPSS version 20 program. The results of this study are dividend variables that positively and significantly influence investors 'decision making in buying shares, right issue variables that are positive but not significant, although positive right issues do not affect investors' decision making in buying shares because they are not significant to decision making, Stock split variables are positive but not significant, although positive stock split does not affect investor decision making in buying shares because it is not significant to decision making